(untitled) (Biological Sciences - PJSIR, 2003)
medium content of organic carbon (0.07 to 0.67%). They had very low content of calcium carbonate (0-1.25%). As evident from the data in Table 1, the available S content in soils ranged from 0.5-18.0 mg kg-1 with a mean value of 7.1 mg kg-1. On the basis of 10 mg kg-1 as the threshold value for available S (Kanwar 1963), 78 per cent of the samples had deficient con- tent of available S. Such a high magnitude of S deficiency may be ascribed to the low organic carbon content and low suphate retention capacity owing to the coarse texture of majority of these soils. Contents of available Zn, Cu, Fe and Mn varied between 0.14-1.74, 0.06-1.5, 1.89-14.50 and 1.03-